Efeitos do exercício resistido na fase hospitalar do pós-operatório de revascularização do miocádio - Ximenes, Nayana Nazaré Pessoa Sousa (2014)
Regular physical activity has been beneficial post - cardiac surgery. Early resistance exercise training improves functional capacity, clinical status, cardiac function and survival of patients, leading to a reduction of the harmful effects of prolonged bed rest, reduced care costs and hospital stay. Objective: To evaluate the effects of resistance exercise during hospital postoperative coronary artery bypass grafting (CABG). Methods: It was performed a randomized controlled trial with 37 patients subjected to isolated CABG between August 2013 and May 2014, distributed by simple drawing into two groups: control group (n = 20) that received conventional physiotherapy and intervention group (n = 17) underwent resistance exercise. Pulmonary function and functional capacity were assessed preoperatively, on discharge from the intensive care unit (ICU) and hospital discharge by spirometry and six minute walk test (6MWT). For statistical analyze were utilized Shapiro-Wilk, Mann-Whitney, Student's t, Fisher and G tests. Variables with p < 0.05 were considered significant. Results: The groups were homogeneous in terms of demographic, clinical, and surgical variables. No effect of resistance exercise on pulmonary function was observed when compared to control group. However, in intervention group it was maintained functional capacity during assessments periods when compared to the control group which was observed significant reducing (p < 0.0001). It was Observed a significant reduction in length of hospital stay (6.3 ± 1 2 vs. 7.6 ± 2.5 days) (p = 0.03). Conclusion: In this study, the resistance exercise during hospital CABG postoperative provided maintaining functional capacity and reduction of hospital stay when compared to conventional physiotherapy.